Beta-amyloid deposition in chronic traumatic encephalopathy - Stein, Thor D.; Montenigro, Philip H.; Alvarez, Victor E.; Xia, Weiming; Crary, John F.; Tripodis, Yorghos; Daneshvar, Daniel H.; Mez, Jesse; Solomon, Todd; Meng, Gaoyuan; Kubilus, Caroline A.; Cormier, Kerry A.; et al. (Acta neuropathologica, 2015)
Chronic traumatic encephalopathy (CTE) is a neurodegenerative disease associated with repetitive mild traumatic brain injury. It is defined pathologically by the abnormal accumulation of tau in a unique pattern that is distinct from other tauopathies, including Alzheimer’s disease (AD). Although trauma has been suggested to increase amyloid β peptide (Aβ) levels, the extent of Aβ deposition in CTE has not been thoroughly characterized. We studied a heterogeneous cohort of deceased athletes and military veterans with neuropathologically diagnosed CTE ( n = 114, mean age at death = 60) to test the hypothesis that Aβ deposition is altered in CTE and associated with more severe pathology and worse clinical outcomes. We found that Aβ deposition, either as diffuse or neuritic plaques, was present in 52 % of CTE subjects. Moreover, Aβ deposition in CTE occurred at an accelerated rate and with altered dynamics in CTE compared to a normal aging population (OR = 3.8, p < 0.001). We also found a clear pathological and clinical dichotomy between those CTE cases with Aβ plaques and those without. Aβ deposition was significantly associated with the presence of the APOE ε4 allele ( p = 0.035), older age at symptom onset ( p < 0.001), and older age at death ( p < 0.001). In addition, when controlling for age, neuritic plaques were significantly associated with increased CTE tauopathy stage ( β = 2.43, p = 0.018), co-morbid Lewy body disease (OR = 5.01, p = 0.009), and dementia (OR = 4.45, p = 0.012). A subset of subjects met the diagnostic criteria for both CTE and AD, and in these subjects both Aβ plaques and total levels of Aβ1-40 were increased at the depths of the cortical sulcus compared to the gyral crests. Overall, these findings suggest that Aβ deposition is altered and accelerated in a cohort of CTE subjects compared to normal aging and that Aβ is associated with both pathological and clinical progression of CTE independent of age.